A first combined electrochemical and modelling strategy on composite carbonate/oxide electrolytes for hybrid fuel cells. (2nd November 2016) - Ricca, C.; Albin, V.; Labat, F.; Adamo, C.; Cassir, M.; Ringuedé, A.
Abstract: Carbonate/oxide composites are very promising electrolyte materials in hybrid fuel cells which could operate at lower temperature than the usual Molten Carbonate Fuel Cells (MCFC) or Solid Oxide Fuel Cells (SOFC), presenting 0.1 S cm −1 at 600 °C. This paper shows some significant and/or unexpected experimental data obtained by impedance spectroscopy, related to the impact of the carbonate/oxide ratios and the heating and cooling cycles in reducing atmospheres on the electrical behaviour of the composites. Based on this peculiar experimental behaviour, combined DFT calculations are selected for acquiring a deeper understanding of the transport mechanisms in such materials. A modelling strategy, in parallel with experimental results, is developed in the present paper. Highlights: Modification of oxide/molten carbonate composites is evidenced in H2 -based atmosphere. Modelling by DFT calculations, of (Li, K)CO3 shows that (001) surface is the most stable. A theoretical strategy is introduced for a deeper understanding of interface phenomena.